The Effect of Online Training Courses of Life Skills on Resilience, locus of control, General Health and Academic Performance of Medical Science Students - Samaneh Mirzaei; Mohammad Hossein Dehghani; Azadeh Aboei; Khadigeh Nasiriani; Faezeh Rashidi; Adel Eftekhari; Zohreh Hesani; Zahra Yazdani; Amir Hossein Ahmadi; Mohsen Gholinataj (Mashhad University of Medical Sciences, 2024)
Background: Learning life skills can improve students' performance. This study aimed to investigate the effect of online life skills training courses on resilience, locus of control, general health, and academic performance at Yazd University of Medical Sciences.Method: This intervention study was performed on 70 third and higher-semester students. For the experimental group, a life skills training program was performed in five sessions during the five weeks. Data collection tools included Connor and Davidson resilience questionnaires, Rutter locus of control, and Goldberg general health and average grade points of the student in the previous and new semester, completed before and one month after the training program. The data were analyzed using SPSS.v22 descriptive statistics and independent and paired t-tests.Results: Before the study, the mean resilience scores of the intervention and control groups were 57.17±2.40 and 58.70±3.58, respectively. After the study, the mean resilience scores of the intervention and control groups were 73.13±2.27 and 59.50±3.50, respectively. Also, the mean scores of the locus of control before and after the study in the intervention and control groups were 10.22 ± 2.04, 11.59 ± 1.32, and 9.02 ± 3.50, 8.95 ± 2.32, respectively. Statistical analysis showed that there was a significant difference between the two groups in terms of all mentioned variables (P<0.0001) after the study.Conclusion: Resilience, locus of control, general health, and student academic performance improved after participating in online training courses on life skills.